Transformation of biosolids to biochar: A case study. Issue 4 (21st December 2018) - Patel, Savankumar; Kundu, Sazal; Paz‐Ferreiro, Jorge; Surapaneni, Aravind; Fouche, Leon; Halder, Pobitra; Setiawan, Adi; Shah, Kalpit
Abstract : This case study examines the feasibility of the production of biochar from biosolids using energy neutral pyrolysis process using ASPEN Plus process modeling followed by a detailed techno‐economic assessment. The modeling exercise demonstrated that the pyrolysis can be energy neutral with moisture content in biosolids as high as 50 wt.%. In the case of moisture content lower than 50%, surplus energy will be available which can be converted to electrical energy; generating additional revenue. Further analysis on the effect of pyrolysis temperature on surplus energy available revealed that surplus energy increased when pyrolysis temperature reached from 450 to 650°C, but it gradually decreased above 650°C. The techno‐economics analysis suggested that biosolids management cost and biochar sale price were the most critical sensitivity factors while capital and operating costs of the pyrolysis unit seemed to be less critical. The positive Net Present Value values in scenario modeling suggest that the conversion of biosolids to biochar using energy neutral pyrolysis process looks promising and is techno‐economically feasible for most of the studied scenarios. © 2018 American Institute of Chemical Engineers Environ Prog, 38:e13113, 2019